Preparation and Assessment of Clomiphene Citrate Liquisolid Tablets for Solubility Enhancement (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Clomiphene citrate is a nonsteroidal ovulation inducer used in the treatment of infertility. This drugbelongs to biopharmaceutical classification system Class-II often possesses challenges concerning solubility orpoor dissolution, drug release, and thereby enhance the bioavailability. Aim: The aim of the study was to improvethe solubility of the drug as well as to make the formulation more feasible liquisolid technique was adopted.Materials and Methods: Here, Avicel PH 102(Q) and Aerosil 200(q) in varying ratios ranging from 5, 10, 20,and 25 were employed as coating and carrier materials (R=Q/q), and their quantities incorporated into formulationwere calculated based on the mathematical formulae developed by Spireas and final powder substrate developedwas compressed into a tablet by direct compression method. Twelve formulations LS1 to LS12 were prepared andsubjected to drug excipient interactions studies, pre-compression, and post-compression studies and comparedwith the marketed formulation. Results and Discussion: The Fourier transform infrared spectroscopy resultsshowed no interaction between drug-excipients. Scanning electron microscopy and X-ray diffractometry analysisindicated that the clomiphene citrate is held within the powder substrate in a solubilized, almost molecularlydispersed state and in liquisolid as an amorphous powder with no signs of instability on storage. An optimizedformulation was selected based on the in vitro, drug release studies. LS2 formulation containing Avicel PH102(Q):Aerosil 200(q) a ratio of 10:1 and drug concentration 10% exhibited the controlled and complete/highestdrug release rate of 96.46% in 30 min in comparison with the marketed product. Conclusion: Thus, we proposethat liquisolid technique can be chosen as the most economical and alternative approach to enhance the solubilityof clomiphene citrate.